5, 10, 15‐Tris(4‐sulfonatophenyl)corrole Synthesis. Issue 38 (7th October 2019) - Caroleo, Fabrizio; Nardis, Sara; Petrella, Greta; Bischetti, Martina; Cicero, Daniel O.; Genovese, Damiano; Mummolo, Liviana; Prodi, Luca; Randazzo, Rosalba; D'Urso, Alessandro; Paolesse, Roberto
Abstract : Two synthetic routes for the preparation of the water soluble 5, 10, 15‐tris(4‐sulfonatophenyl)corrole are reported. The first approach explores the chlorosulfonation reaction on the phosphorus complex of 5, 10, 15‐tris(4‐trimethylsilylphenyl)corrole. Following this route, the P complex of the target corrole has been obtained in low yields, while the major product was the tetrasubstituted complex, with the additional sulfonyl group regioselectively introduced at the 2‐position. To widen the scope of the reaction, the direct preparation of the 5, 10, 15‐tris(4‐sulfonatophenyl)corrole has been pointed out, affording both the target corrole and the intermediate chlorosulfonyl derivative in reasonable yields. The photophysical properties and the protonation equilibria of both corroles have been investigated, showing that 5, 10, 15‐tris(4‐sulfonatophenyl)corrole does not aggregate in acidic solutions, different from the analogous porphyrin. Abstract : A lonely corrole : Different from the analogous porphyrin, the water soluble 5, 10, 15‐tris(4‐sulfonatophenyl)corrole does not aggregate in water solutions, remaining in the monomeric form even when the zwitterionic species is formed at low solution pH. Two synthetic routes for the preparation of the water soluble 5, 10, 15‐tris(4‐sulfonatophenyl)corrole are reported.